Strategy for diagnosis and correction of vaginal dysbiosis in terms of preparation of pregnant for planned cesarean section and prevention of postpartum endometritis - Voronin K.V.; Alale A.M.; Alale I.I.; Dzyba Y.N. (Medičnì Perspektivi)
Clinical features of vaginal dysbiosis as a factor in the high risk of septic complications, especially in pregnant women diagnosed with anaerobic vaginal dysbiosis were examined. Low efficiency of the traditional methods of treating bacterial dysbiosis, a high rate of recurrences and the risk of preterm delivery dictate the need to find alternative methods of treatment and prevention of antenatal and post-natal complications. The widespread introduction of caesarean section into obstetric practice contributed to the reduction of perinatal loss. However, together with the expansion of indications for cesarean section, increase in the frequency and severity of post-natal chronic inflammatory diseases is associated. The number of purulent-inflammatory diseases in the early postoperative period and in the long-term period after C-section is large, reaching 3,3-54,3%. Postpartum period, even in physiological course and particularly in the presence of risk factors is favorable for the development of infectious complications. Almost all the authors identify caesarean section as a significant risk factor for postpartum endometritis, since, making only 10 - 20% of the total number of deliveries, cesarean section causes 80% of all postpartum endometritis. We propose a diagnostic algorithm, drug correction and prevention for this common group of patients.